Comorbidity of Axis I disorders in a sample of at-risk, problem, andpathological gamblers - Anja Bischof (2014)
Background. Pathological gambling has – as the first behavioral addiction – recently been added to the substance-related disorders in the Diagnostic and Statistical Manual, fifth edition (DSM-5). There are a variety of factors that are associated with pathological gambling as age, gender, impulsivity, and mental disorders. The present study aims to highlight a specific aspect of problematic gambling: the comorbidity of psychiatric conditions in at-risk, problem, and pathological gamblers. Methods. Based on a general population based sample of 15,023 participants of the study “Pathological Gambling and Epidemiology” (PAGE), the present study analyzed comorbid Axis-I disorders among 164 adult gamblers. Data of this survey were compared with the distribution of psychiatric conditions in a general population sample. Results. Results are displayed in the published article “Comorbid Axis I-disorders among subjects with pathological, problem, or at-risk gambling recruited from the general population in Germany” (Journal: Psychiatry Research, E-pub ahead of print). Lifetime prevalence of any psychiatric disorder was 93.6% among pathological (5-10 DSM-IV criteria), 83.5% among problem (3-4 DSM-IV criteria), and 81.0% among at risk gamblers (1-2 DSM-IV criteria). Conditional Odds Ratios (COR) for having a comorbid disorder were 3.5 (95%-Confidence interval, CI 2.6-4.6) in at-risk gamblers, 4.9 (CI 3.3-7.3) in problem gamblers, and 4.6 (CI 3.0-6.9) in pathological gamblers compared to the general population. Conclusions. The present study was the first one to compare subgroups of gamblers (at-risk, problem, and pathological gamblers) to a sample of the general population regarding Axis I-disorders. The results showed that prevalence proportions of psychiatric conditions were extraordinary high in all three groups of gamblers compared to the general population. These data can help to understand the complexity of problematic gambling and might help to foster a treatment service that reaches gamblers at an early stage of the disorder. Early interventions and prevention programs addressing subthreshold gambling problems appear to be necessary. Longitudinal research concerning the persistence of problematic gambling is required.